An Unlikely Alliance: How Experts and Industry Transformed Consumer Credit Policy in the Early Twentieth Century United States. Issue 4 (1st December 2015) - Anderson, Elisabeth; Carruthers, Bruce G.; Guinnane, Timothy W.
Abstract : Despite the recently demonstrated importance of consumer credit for the economic health of nations and families, little is known about the history of consumer credit markets and their regulation. An important chapter in the history of consumer credit regulation came between 1909 and 1941, when policy experts at the Russell Sage Foundation (RSF) engaged in a national campaign to transform small loan markets and policy in the United States. Concentrating its efforts on state-by-state passage of the Uniform Small Loan Law, the foundation's political success hinged upon an alliance with the American Association of Personal Finance Companies. While most scholarship portrays experts as being dominated or co-opted by industry, our case provides a countervailing example. Far from controlling RSF experts, lenders became dependent on the foundation for legitimating their political lobbying and their business activities. We explain how the foundation built its expert reputation through a process of reputational entrepreneurship, and we trace how RSF experts deployed this reputation as a power resource in their negotiations with small loan lenders.